Vedic Sutras Mathematics with Application in Differentiation (International Journal of Scientific Research in Science and Technology, 2024)
Vedic Mathematics, rooted in ancient Indian texts, offers a unique and efficient approach to solving complex mathematical problems. This paper explores the application of Vedic principles in modern calculus, specifically focusing on derivatives and integration. By applying Vedic methods, such as the Urdhva Tiryak Sutra (vertical and crosswise multiplication) and Paravartya Sutra (transposition), we demonstrate how these can simplify and expedite processes in differentiation and integration. The study provides practical examples where these techniques are applied to common calculus problems, highlighting their potential to enhance problem-solving efficiency in higher mathematics.